Could Time Detect a Faking-Good Attitude? A Study With the MMPI-2-RF - Roma, Paolo; Verrocchio, Maria C.; Mazza, Cristina; Marchetti, Daniela; Burla, Franco; Cinti, Maria E.; Ferracuti, Stefano (Frontiers in Psychology, 2018)
BACKGROUND AND PURPOSE. Research on the relationship between response latency (RL) and faking in self-administered testing scenarios have generated contradictory findings. We explored this relationship further, aiming to add further insight into the reliability of self-report measures. We compared RLs and T-scores on the MMPI-2-RF (validity and restructured clinical [RC] scales) in four experimental groups. Our hypotheses were that: the Fake-Good Speeded group would obtain a different completion time; show higher RLs than the Honesty Speeded Group in the validity scales; show higher T-Scores in the L-r and K-r scales and lower T-scores in the F-r and RC scales; and show higher levels of tension and fatigue. Finally, the impact of the speeded condition in malingering was assessed. MATERIALS AND METHODS. The sample was comprised of 135 subjects (M = 26.64; SD = 1.88 years old), all of whom were graduates (having completed at least 17 years of instruction), male, and Caucasian. Subjects were randomly assigned to four groups: Honesty Speeded, Fake-Good Speeded, Honesty Un-Speeded, and Fake-Good Un-Speeded. A software version of the MMPI-2-RF and Visual Analogue Scale (VAS) were administered. To test the hypotheses, MANOVAs and binomial logistic regressions were run. RESULTS. Significant differences were found between the four groups, and particularly between the Honest and Fake-Good groups in terms of test completion time and the L-r and K-r scales. The speeded condition increased T-scores in the L-r and K-r scales but decreased T-scores in some of the RC scales. The Fake groups also scored higher on the VAS Tension subscale. Completion times for the first and second parts of the MMPI-2-RF and T-scores for the K-r scale seemed to predict malingering. CONCLUSIONS. The speeded condition seemed to bring out the malingerers. Limitations include the sample size and gender bias.